The Idea of Organizational Resilience in the Face of Cybercrime - Walentek, Dorota; Jelonek, Dorota (Idea rezyliencji organizacyjnej w obliczu cyberprzestępczości, 2023)
The digital transformation process, deepened by the outbreak of the COVID-19 pandemic, completely changes the current reality of the organization in global terms. Using digital solutions has a number of advantages, but it is also associated with numerous cyber threats. In the face of these threats, digital resilience has become a kind of business imperative. The aim of the article is to determine the level of knowledge of the organization’s employees about cyber threats and the degree of their preparation for potential threats of this type. The study showed an insufficient level of recognition of cyber threats by employees of the organization. It was found that employees were not adequately prepared for potential threats by the employer, which consisted, among others, in the fact that training on digital threats was conducted too rarely. Many employees do not apply appropriate forms of data and document protection. The above conclusions should encourage managers to ensure a higher level of employee education on cybercrime, and thus to build a more digitally resilient organization.
Walentek, D., and Jelonek, D. (2023). The Idea of Organizational Resilience in the Face of Cybercrime. In M. Hajdas (Ed.), Game Changers in Management (pp. 54-71). Publishing House of Wroclaw University of Economics and Business.
Keywords: organisational resilience; cybercrime; cyber security; rezyliencja organizacyjna; cyberprzemoc; cyberbezpieczeństwo